(untitled) (American Journal of Research in Humanities and Social Sciences, 2023)
This article discusses innovative ways to teach English as a second language to school students. Nowadays, language learning is one of the most urgent issues, the article discusses the methods of teaching English to schoolchildren in various new methods, including teaching with the help of games.